2022
DOI: 10.3390/en15103689
|View full text |Cite
|
Sign up to set email alerts
|

Direct Power Control Based on Modified Sliding Mode Controller for a Variable-Speed Multi-Rotor Wind Turbine System Using PWM Strategy

Abstract: A robust and improved control scheme of a variable speed multi-rotor wind turbine (MRWT) system with a doubly fed asynchronous generator (DFAG) is displayed in this work. In order to improve the performances and effectiveness of the traditional direct power control (DPC) strategy of the DFAG, a new kind of sliding mode controller (SMC) called modified SMC (MSMC) is proposed. The most important advantage of the DPC-MSMC strategy is to reduce the power ripples and improve the quality of the currents provided to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 80 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Recently, renewable energy sources have been used to control active and reactive power outputs using existing technologies and strategies [32][33][34][35][36][37]. However, the existing operational renewable energy sources in South Korea do not require this function at the time of connection.…”
Section: Inertia and Non-synchronous Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, renewable energy sources have been used to control active and reactive power outputs using existing technologies and strategies [32][33][34][35][36][37]. However, the existing operational renewable energy sources in South Korea do not require this function at the time of connection.…”
Section: Inertia and Non-synchronous Generationmentioning
confidence: 99%
“…A decrease in system inertia degrades the frequency stability by increasing the rate of change of frequency (RoCof) and degrading the frequency nadir [31]. Recently, renewable energy sources have been used to control active and reactive power outputs using existing technologies and strategies [32–37]. However, the existing operational renewable energy sources in South Korea do not require this function at the time of connection.…”
Section: Non‐synchronous Generation In South Koreamentioning
confidence: 99%
“…These control strategies differ in principle, simplicity, ease of implementation, cost, and durability. Several practical works dealt with the control of APF, [63][64][65][66] where two levels of APF were used in these works to simplify the proposed systems. These works showed that the control strategy has a major role in improving the quality of power and current together.…”
Section: Introductionmentioning
confidence: 99%
“…The DPC and DTC strategies are among the most prominent linear control strategies used in the field of controlling electrical machines, especially in the field of renewable energies. These strategies depend on the use of a lookup table (LT) to regulate and control the operation of the inverter machine, and traditional controllers of the type hysteresis comparators (HCs) are used to control the characteristic quantities (Energy and Torque) [11]. Therefore, there are no complex calculations in these strategies that hinder their application to the systems.…”
Section: Introductionmentioning
confidence: 99%